2016
DOI: 10.1038/srep29657
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of plant DNA replication based on PCNA visualization

Abstract: DNA replication is an essential process for the copying of genomic information in living organisms. Imaging of DNA replication in tissues and organs is mainly performed using fixed cells after incorporation of thymidine analogs. To establish a useful marker line to measure the duration of DNA replication and analyze the dynamics of DNA replication, we focused on the proliferating cell nuclear antigen (PCNA), which functions as a DNA sliding clamp for replicative DNA polymerases and is an essential component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 29 publications
(43 reference statements)
3
48
0
Order By: Relevance
“…In the cell cycle, the synthesis of PCNA is important for the entry of cells into the S phase from the G0 and G1 phases. PCNA expression has been demonstrated to be increased in the late stages of cell entry into the G1 phase, reaches its peak in the S phase, and decreases in the G2 and M phases (23). The results of the present study demonstrated that expression of PCNA was significantly increased in the surgery group compared with the normal and the medical adhesive spray groups, indicating that the medical adhesive inhibited cell proliferation following surgery.…”
Section: Discussionsupporting
confidence: 48%
“…In the cell cycle, the synthesis of PCNA is important for the entry of cells into the S phase from the G0 and G1 phases. PCNA expression has been demonstrated to be increased in the late stages of cell entry into the G1 phase, reaches its peak in the S phase, and decreases in the G2 and M phases (23). The results of the present study demonstrated that expression of PCNA was significantly increased in the surgery group compared with the normal and the medical adhesive spray groups, indicating that the medical adhesive inhibited cell proliferation following surgery.…”
Section: Discussionsupporting
confidence: 48%
“…To monitor the progression of the cell cycle in living cells, we used transgenic lines expressing RAD54‐EYFP and PCNA1‐tdTomato (Figure c). Arabidopsis PCNA1 shows distinct subcellular localization patterns, which are whole, dotted or speckled indicating G 1 or G 2 phase, early S phase and late S phase during the cell cycle, respectively (Yokoyama et al ., ). The whole pattern is defined by the uniform distribution of PCNA1 in the nucleoplasm.…”
Section: Resultsmentioning
confidence: 97%
“…Cells in early S-phase, characterized by small PCNA dots, could not be clearly distinguished under our imaging conditions. Nevertheless, the duration of the speckle-stage is comparable to mitotic cells 43 , indicating that the pre-meiotic S-phase is not substantially longer than the S-phase of mitotic cells. This is in contrast to observations in other organisms, where pre-meiotic S-phase was reported to be at least twice as long as mitotic S-phase 44,45 .…”
Section: Use Of Live Imaging In Gene Function Studiesmentioning
confidence: 87%
“…S-phase in Arabidopsis can be monitored by proliferating cell nuclear antigen (PCNA). PCNA exhibits a disperse nuclear localization throughout the cell cycle but forms nuclear foci ranging from small dots to large nuclear speckles during S-phase 43 . Live imaging of pre-meiotic cells expressing ASY1:eYFP and PCNA:tagRFP markers showed a reorganization of PCNA from a diffused signal to nuclear speckles, which were detectable for approximately 90 min ( Fig.…”
Section: Use Of Live Imaging In Gene Function Studiesmentioning
confidence: 99%